Settlement of conflict, recognition and enforcement of international arbitral awards / Mohamad Sabri Yusoh and Mohd Kamal Azman Jusoh - Yusoh, Mohamad Sabri; Jusoh, Mohd Kamal Azman (2009)
Conflict exists by the day due to the existence of various human needs, greed and differences in one's background and upbringing. Differences are natural and even beneficial but must be kept in control so as not to cause any unnecessary repercussion. One must seek readiness and find amicable solution to their conflict in such a way which is less painful and non destructive.